CHALLENGES ON FEMALE EMPLOYEES AT PT PERTAMINA GEOTHERMAL ENERGY AREA LAHENDONG - Natalytha Kimberly Liling; Merinda Pandowo; James Massie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
In nowadays the presence of women is needed to bring different perspectives and solutions especially in the workplace that dominated by male workers. This research concern to challenges that female employees faced during their career in the workplaces such as glass ceiling, discrimination, sexual harassment and work-life balance also how to overcome the challenges. This research used qualitative approach. From 24 employees author took 16 informants due the sampling techniques that be used in this study is purposive sampling with the criteria of the informants those who works more than or at least 5 years. The findings of this research are ages discrimination, sexual harassment and work-life balance as a challenges for female employees at PT Pertamina Geothermal Energy Area Lahendong. Glass ceilings are not considered a challenge because the company only promotes employees who meet the qualifications for the position without see their gender. Those challenges influenced the employees performance and employees satisfactions to overcome these challenges the female employees at PT Pertamina Geothermal Energy Area Lahendong need to develop themselves, managed time well between work and family so that it can be balanced.Â Keywords: challenges, female employees, glass ceiling, discrimination, sexual harassment, work-life balance